USG guided indices as a tool for prediction of difficult airway in obese: an observational study - Paleti Sophia; Kuppili Geethika; Jalaja Praveena B.; Vishnuvardhan A. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Now a days, Ultrasound has been the gold standard and an invaluable tool in the field of regional anaesthesia, especially for upper limb and truncal blocks where general anesthesia is associated with high risk and also in patients posted for general anesthesia with anticipated difficult airway. Recently, few studies have published the importance of Ultrasound in the evaluation of airway and related procedures. Aim of this study is to evaluate the use of USG guided indices for prediction of difficult airway in obese patients and correlating them with clinical parameters. Methods: This study was a prospective observational study done in a tertiary health care center, Government General hospital, Kakinada over a duration of two months from August 2022 to September 2022. Eight Ultrasound parameters like tongue thickness, skin to hyoid distance, pre-epiglottic space, skin to midpoint of vocal cords, skin to thyroid isthmus, anterior soft tissue thickness at suprasternal notch, hyomental distance and thyromental distance were correlated with clinical evaluation (Cormacke-lehane grading) in this study and conclusions were drawn. Results: Out of 30 cases studied, 20 (70%) were predicted to be difficult with Ultrasound airway examination and 16 (53.3%) were found to have difficulty in intubation clinically. Conclusions: The following USG indices like pre-epiglottic space, Skin to midpoint of vocal cords, Anterior soft tissue thickness at Suprasternal notch, Hyomental distance in mid-extended position and thyromental distance were found to be clinically correlated to predict difficult airway and intubation in obese patients.